2020
DOI: 10.1021/acs.joc.0c00658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Distance between Radical Sites on the Reactivities of Aromatic Biradicals

Abstract: Coupling of the radical sites in isomeric benzynes is known to hinder their radical reactivity. In order to determine how far apart the radical sites must be for them not to interact, the gasphase reactivity of several isomeric protonated (iso)quinoline-and acridine-based biradicals was examined. All the (iso)quinoliniumbased biradicals were found to react slower than the related monoradicals with similar vertical electron affinities (i.e., similar polar effects). In sharp contrast, the acridinium-based biradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The vertical electron affinities (EA v ) and singlet triplet splittings ( ~ES-T ) were calculated as described in the literature. [27,33] The EA v values for triradicals were calculated for the radical site that, based on calculations, gains most electron density upon addition of an electron to the triradical. The distortion energy values (ΔE 2.3 Å ) were calculated at the UBLYP/ cc-pVDZ level of theory.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The vertical electron affinities (EA v ) and singlet triplet splittings ( ~ES-T ) were calculated as described in the literature. [27,33] The EA v values for triradicals were calculated for the radical site that, based on calculations, gains most electron density upon addition of an electron to the triradical. The distortion energy values (ΔE 2.3 Å ) were calculated at the UBLYP/ cc-pVDZ level of theory.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the reactivity of biradicals of the type discussed above are controlled by several parameters. [25][26][27] The calculated vertical electron affinity (EA v ) of the radical site has been reported to be a significant reactivity controlling factor for polar (charged and uncharged) mono-and biradicals. [25][26][27][28][29] A high EA v stabilizes an important polar resonance structure of the transition states of atom abstraction reactions (i. e., H atom abstraction) and therefore lowers the transition state energy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations